Emerging Sonodynamic Therapy‐Based Nanomedicines for Cancer Immunotherapy. Issue 2 (27th November 2022) - Yang, Yunrong; Huang, Jia; Liu, Min; Qiu, Yige; Chen, Qiaohui; Zhao, Tianjiao; Xiao, Zuoxiu; Yang, Yuqi; Jiang, Yitian; Huang, Qiong; Ai, Kelong
Abstract: Cancer immunotherapy effect can be greatly enhanced by other methods to induce immunogenic cell death (ICD), which has profoundly affected immunotherapy as a highly efficient paradigm. However, these treatments have significant limitations, either by causing damage of the immune system or limited to superficial tumors. Sonodynamic therapy (SDT) can induce ICD to promote immunotherapy without affecting the immune system because of its excellent spatiotemporal selectivity and low side effects. Nevertheless, SDT is still limited by low reactive oxygen species yield and the complex tumor microenvironment. Recently, some emerging SDT‐based nanomedicines have made numerous attractive and encouraging achievements in the field of cancer immunotherapy due to high immunotherapeutic efficiency. However, this cross‐cutting field of research is still far from being widely explored due to huge professional barriers. Herein, the characteristics of the tumor immune microenvironment and the mechanisms of ICD are firstly systematically summarized. Subsequently, the therapeutic mechanism of SDT is fully summarized, and the advantages and limitations of SDT are discussed. The representative advances of SDT‐based nanomedicines for cancer immunotherapy are further highlighted. Finally, the application prospects and challenges of SDT‐based immunotherapy in future clinical translation are discussed. Abstract : Biological characteristics of the tumor immune microenvironment (TIM) and the mechanisms of immunogenic cell death (ICD) are described. Anticancer mechanisms of sonodynamic therpy (SDT) and its advantages and limitations are summarized. Represantative advances of SDT based nanomedicines for cancer immunotherapy are highlighted. Urgent challenges and clinical application prospects of SDT based immunotherapy are discussed.